P214 Cine MRI assessment of colonic motility in patients with ulcerative colitis associated constipation. (30th January 2023) - Miller, C; Taylor, S; Emmanuel, A; Zarate-Lopez, N; Pakpoor, J; Fitzke, H; Menys, A; Holmes, J; Atkinson, D; Markus, J; Blad, W; Bloom, S
Abstract: Background: Constipation may be a feature of ulcerative colitis (uc) especially in left sided or distal disease. UC associated constipation (UCAC) can cause significant morbidity; treatment is typically with dietary fibre changes and laxatives. Diagnosis may be challenging but adequate treatment may improve clinical outcomes. The cause is incompletely understood with few studies of motility and transit. Study populations often having heterogenous groups, with limited assessment of right sided colonic motility. Cine MRI is a novel technique that can assess pan-colonic motility. Using this technique, We aim to investigate regional colonic motility in patients with active disease and UCAC symptoms. Methods: The study was performed prospectively with 30 participants at a single-centre. Disease extent was confirmed to be distal to the splenic flexure. Active disease was defined as a faecal calprotectin >250, partial Mayo score ≥ 4 (rectal bleeding score ≥ 1) or an endoscopic mayo score >1. The 3 groups comprised 10 healthy controls with no symptoms of IBS/ constipation, 11 patients with active uc with symptoms of UCAC, and 9 patients with active uc without symptoms of UCAC. UCAC subjects met American Gastroenterology Association constipation criteria. Exclusion criteria comprised the use of drugs affecting motility, concomitant GI conditions, and recent laxative use. Subjects underwent two constipation questionnaires. Subjects were fasted > 8 hours and subjects consumed 1.4 litres of 2% mannitol over 90 minutes prior to a morning MRI scan. Post drink cine MRI was not acquired until the mannitol had reached the ascending colon (AC). Images were acquired over the entire abdomen for 10 minutes and using GI Quant software®(Motilent) regional colonic motility was assessed (Figure A), generating a motility index (MI) score (range 0-1000). Kruskal-Wallis and Mann-Whitney U (with Holm-Bonferroni correction) statistics were used. Results: Baseline characteristics and questionnaire scores are outlined in Figure B and MI scores in Figure C. There was no clear trend for differences in motility in the caecum or AC. In the transverse colon (TC) there was a trend to reduced MI in patients with UCAC compared to controls which was nearly significant (p=0.06). Conclusion: We present a new technique for assessing regional colonic motility in patients with uc with a 10-minute scan, and offers a method to study the dysmotility that underpins UCAC. Motility appears to be reduced in the TC in patients with left sided uc and symptoms of UCAC compared to controls. Although not statistically significant this suggests hypomotility may be a contributing factor to UCAC. It suggests that stimulants/prokinetic may be more effective than change to dietary fibre in its treatment.